Factors Affecting Illegal Land-use Changes in Residential Areas: (Case Study: District 6 of Tehran) - Rama Ghalambordezfooly; Fatemeh Hosseini (Journal of Regional and City Planning, 2023)
Today, understanding the trend of land-use changes and its contributing factors is one of the important issues in urban land-use planning and urban management policies. Not all land-use changes comply with urban development plan regulations. Illegal land-use changes, especially in residential areas, are often implemented to reduce the municipality tax for small businesses in large cities in Iran. This trend has become a source of income for municipalities through fine acquisition. The objective of this study was to identify the factors contributing to incompatible and illegal land-use changes in the case study of District 6 in Tehran. The research method used in this study was descriptive-analytical. The data was collected using a questionnaire and a field study. The data were analyzed using the Pearson correlation test and confirmatory factor analysis using the equation modeling technique in the LISREL software. According to the research findings, escape from the traffic scheme zone, with a coefficient load factor of 0.86, and economic profitability, with a coefficient load factor of 0.84, were the most important factors motivating illegal land-use changes in the residential areas in this case study (District 6, Tehran). The main conclusion of this research is the need for change in Tehran urban policies for mitigation of urban planning violations. Specially in this case, the impact of the traffic scheme zone in Tehran should be considered. Another suggestion is the adoption of new urban policies related to taxes on unauthorized activities in residential areas that can counteract the market response to possible changes.